THE EFFECT OF LAND SUBSIDENCE TO CHANGE IN THE MOST EXTENSIVE PUDDLE IN SEMARANG - Pratikso .; Soedarsono . (International Conference on Coastal and Delta Areas, 2015)
Semarang city can generally be divided into two areas, namely urban areas over the hilly soil conditions, loud and reaches a height of 350m above sea level, and the lower town is a fine-grained alluvial plains. In the area, under the terms of the geography, the terrain is flat, water-saturated, its location is on the waterfront and is traversed by several rivers, most of the land in the form of settlements that grows naturally and irregularly, the land suffered subsidence (land subsidence) because of the extra load on it and excessive groundwater, based on current conditions, in general most alluvial Semarang is frequent inundation of rain and tides. To be able to plan land use and economic activities well, it is necessary to note changes in broad pools of the region because of land subsidence due to consolidation.The purpose of this study is intended to create a map of inundation due to land subsidence and predicting the area inundation will occur from time to time. This study focuses on getting the data of land subsidence due to the consolidation of the land that became the main cause of subsidence resulting in the addition of extensive flooding. From these data, it is converted between land subsidence with water level inundation occurred.This research is conducted by conducting land drilling with drill machine in 24 points to a depth of 30m to obtain soil samples in five sub-districts of North Semarang, Semarang Genuk, East Semarang, Semarang Gayamsari and Central Semarang. Samples are obtained and then tested the mechanical properties of the soil and the soil in soil mechanics laboratory of Unissula. From the lab test results are then analyzed to determine the amount of land subsidence due to consolidation. Finally, the writer conducts extensive analysis of changes in inundation as a result of subsidence by using GIS.Implementation of this research will result a map of inundation area in Semarang and amended from time to time. This study is planned for three years. In the first year on the stage of 70% has been implemented with the drilling machine on 8 points with a depth of 30m. Furthermore, the sample has been tested and mechanical properties of the soil in Soil Mechanics Laboratory of Unissula. From the analysis it appears that the more north (toward the ocean) the greater the decline, but the decline in the longer time.Keywords: consolidation, reduction in area, large puddles.